LIFE SATISFACTION AMONG OLD AGED PEOPLE ATTENDING FAUJI FOUNDATION HOSPITAL: Life Satisfaction Among Old Aged People - Riaz, Mehwish; Sultana, Abida; Tariq, Aisha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine life satisfaction in old age people attending Fauji Foundation Hospital and to assess relationship of socio-demographic variables on life satisfaction of old aged people.Study Design: Cross sectional study.Place and Duration of Study: Fauji Foundation Hospital Rawalpindi from Feb to Aug 2018.Methodology: A total of 347 individuals were included by using non-probability consecutive sampling. The participants of the 60 years or more attending Fauji foundation hospital, being mentally sound and having comprehensive under-standing without hearing aid were included in the study. Questionnaire was given to respondents including demographic profile and Urdu version of Life Satisfaction Scale for assessing the life satisfaction in old age.Results: The total sample mean life satisfaction score was 14.95 ± 6.54. 5 (1.5%) people were extremely satisfied, 27 (8.4%) were satisfied, 117 (36 %) were dissatisfied and 63 (19.1%) were extremely dissatisfied.Conclusion: Life satisfaction was found statistically significant with female gender, older age 70-80 years, being un married, primary education, monthly income of less than 10,000 and being unemployed.